Disclosure form of potential conflicts of interest - journal "Morphologia", Editorial office (Морфологія / Morphologia / Morfologìâ, 2014)
Making manuscripts for filing in international journals often takes a long period of time and requires knowledge of the basics of generally accepted standards for publishing activities. Some accompanying documents have not been used in the practice of domestic editions up until recently and are therefore not accustomed to our authors and cause difficulties for them. Among other things, this is the Conflict of Interest - a document that many editors require in an arbitrary form.